Taxonomic revision of the Menticirrhus americanus (Linnaeus, 1758) and M. littoralis (Holbrook, 1847) (Percomorphacea: Sciaenidae) species complexes from the western Atlantic - Marceniuk, Alexandre Pires; Caires, Rodrigo Antunes; Rotundo, Matheus Marcos; Catarine Dantas Cerqueira, Najila Nolie [UNESP]; Siccha-Ramirez, Raquel; Wosiacki, Wolmar Benjamin; Oliveira, Claudio [UNESP] (Magnolia Press, 2020)
The genus Menticirrhus is widely distributed in the Neotropical region, where its species are common and abundant in shallow coastal waters and estuaries. The diversity, biogeography, and evolutionary relationships of the Menticirrhus species are still poorly known, due primarily to the difficulty of differentiating the species, given the broad similarities in their external morphology. The present study is based on the analysis of morphological and molecular data, with the examination of type specimens and a comprehensive collection of non-type specimens from an ample geographic range. These analyses indicated that two widely distributed Western Atlantic species, Menticirrhus americanus and M. littoralis, represent species complexes. The M. littoralis species complex is characterized by the absence of dark bars on body side, and a smaller, light-colored pectoral fins, that barely reaching the tip of the depressed pelvic fins, with fewer pectoral-fin rays. This complex includes three species: M. littoralis, found in the Gulf of Mexico, M. gracilis, from the southeastern and southern coast of South America, and a new species, described here, from the northern to eastern Brazilian coast. The M. americanus species complex is characterized by the presence of dark bars on body side, and a large, dark pectoral fin, that surpass the tip of the depressed pelvic fin, with more pectoral-fin rays. This complex has two species, M. americanus, which occurs on the east coast of the United States and in the Gulf of Mexico, and M. martinicensis, found from Caribbean to Argentina, that represents a cryptic allopatric species. An identification key to all species of the genus is presented.
Keywords: New species; Menticirrhus gracilis; Menticirrhus martinicensis; cryptic species; DNA barcode; biogeography